Risk Factors Associated with MDR-TB at the Onset of Therapy among New Cases Registered with the RNTCP in Mumbai, India - Atre, Sachin R. (2011)
BACKGROUND: Multidrug-resistant TB (MDR-TB) has emerged as a major threat to global TB control efforts in recent years. Facilities for its diagnosis and treatment are limited in many high-burden countries, including India. In hyper-endemic areas like Mumbai, screening for newly diagnosed cases at a higher risk of acquiring MDR-TB is necessary, for initiating appropriate and timely treatment, to prevent its further spread. OBJECTIVE: To assess risk factors associated with MDR-TB among Category I, new sputum smear-positive cases, at the onset of therapy. MATERIALS AND METHODS: The study applied an unmatched case-control design for 514 patients (106 cases with MDR-TB strains and 408 controls with non-MDR-TB strains). The patients were registered with the Revised National Tuberculosis Control Program (RNTCP) in four selected wards of Mumbai during April 2004-January 2007. Data were collected through semi-structured interviews and drug susceptibility test results. RESULTS: Multivariate analysis indicated that infection with the Beijing strain (OR = 3.06; 95% C.I. = 1.12-8.38; P = 0.029) and female gender (OR = 1.68; 95% C.I. = 1.02-2.87; P = 0.042) were significant predictors of MDR-TB at the onset of therapy. CONCLUSION: The study provides a starting point to further examine the usefulness of these risk factors as screening tools in identifying individuals with MDR-TB, in settings where diagnostic and treatment facilities for MDR-TB are limited.